Understanding Human-wildlife conflict and its impact on agroecology transition in Zimbabwe - Trust, Bio Hub; Chimonyo, Vimbayi G.P.; Sibanda, Telma; Matangi, Dorcas (CGIAR System Organization, 2024)
Human-wildlife conflict (HWC) presents a critical challenge to agroecological transitions in Mbire District, where communities depend heavily on agriculture and cultural traditions such as wild harvest. Situated in a region with a rich biodiversity that includes elephants, lions, baboons, and crocodiles among other animals, Mbire's rural population faces frequent and often dangerous interactions with wildlife. These encounters not only endanger human lives and livestock but also disrupt crop production, compromising food security and stability in an area where agriculture sustains livelihoods and cultural practices. Wildlife intrusions devastate crop fields and imperil livestock, leading communities to adopt various mitigation strategies that range from traditional deterrent methods to collaboration with government agencies. However, these strategies are often limited by external policies and insufficient resources, exacerbating local frustrations and hardships. This report, part of BI-HUB TRUST contribution to the CGIAR Agroecology initiative, documents dialogues among community of elders and stakeholders, highlighting the integration of Indigenous Knowledge Systems (IKS) and the need for effective HWC solutions within agroecological transitions. The elders' dialogues, a central part of BIOHUB’s engagement, illustrate the community’s reliance on traditional spiritual practices to coexist with wildlife, drawing on rituals, ancestral guidance, and community-wide customs to maintain balance within their ecosystem. For instance, villagers employ traditional deterrents, such as burning elephant dung or constructing makeshift barriers, to minimize crop losses. These practices, however, are frequently insufficient in the face of increasing wildlife pressures, partly driven by land encroachment and ecological changes that disrupt natural wildlife habitats, compelling animals to venture closer to human settlements. The continuation of these traditional methods is hampered by legal and bureaucratic restrictions, as community members often lack authority to make immediate decisions about wildlife management. Government policies on wildlife conservation are perceived locally as favoring animal protection over human safety, thereby straining relations between conservation agencies and rural populations. These policies, which limit communities' capacity to manage wildlife, impede the development of local, context-specific solutions to HWC and hinder the progress of agroecological transitions. The report underscores that a successful agroecological transition in Mbire must address HWC by aligning national policy frameworks with community belief system, needs and fostering a collaborative approach that respects traditional knowledge. By integrating ecological stewardship with indigenous practices, the community dialogues reveal pathways towards more resilient agricultural systems that honor local cultural values, reduce wildlife conflicts, and support sustainable agricultural practices. This approach seeks to transform HWC from a source of division into a component of Mbire’s agroecological resilience, bolstering sustainable ecosystem and community cohesion.